Trypanosoma cruzi Calreticulin Is a Lectin That Binds Monoglucosylated Oligosaccharides but Not Protein Moieties of Glycoproteins - Labriola, Carlos (The American Society for Cell Biology, 1999)
Trypanosoma cruzi is a protozoan parasite that belongs to an early branch in evolution. Although it lacks several features of the pathway of protein N-glycosylation and oligosaccharide processing present in the endoplasmic reticulum of higher eukaryotes, it displays UDP-Glc:glycoprotein glucosyltransferase and glucosidase II activities. It is herewith reported that this protozoan also expresses a calreticulin-like molecule, the third component of the quality control of glycoprotein folding. No calnexin-encoding gene was detected. Recombinant T. cruzi calreticulin specifically recognized free monoglucosylated high-mannose-type oligosaccharides. Addition of anti-calreticulin serum to extracts obtained from cells pulse–chased with [(35)S]Met plus [(35)S]Cys immunoprecipitated two proteins that were identified as calreticulin and the lysosomal proteinase cruzipain (a major soluble glycoprotein). The latter but not the former protein disappeared from immunoprecipitates upon chasing cells. Contrary to what happens in mammalian cells, addition of the glucosidase II inhibitor 1-deoxynojirimycin promoted calreticulin–cruzipain interaction. This result is consistent with the known pathway of protein N-glycosylation and oligosaccharide processing occurring in T. cruzi. A treatment of the calreticulin-cruzipain complexes with endo-β-N-acetylglucosaminidase H either before or after addition of anti-calreticulin serum completely disrupted calreticulin–cruzipain interaction. In addition, mature monoglucosylated but not unglucosylated cruzipain isolated from lysosomes was found to interact with recombinant calreticulin. It was concluded that the quality control of glycoprotein folding appeared early in evolution, and that T. cruzi calreticulin binds monoglucosylated oligosaccharides but not the protein moiety of cruzipain. Furthermore, evidence is presented indicating that glucosyltransferase glucosylated cruzipain at its last folding stages.